Effectiveness of Merging Compensation Claims in Criminal Cases: A Case Study of Decision Number 196/Pid.Sus/2021/PN. Jkt.Utr. - Lengkong, Lonna Yohanes; Situmeang, Tomson; Washington, Andree (International Journal of Social Service and Research, 2024)
This study investigates the Efficiency of Combining Compensation Claims in Criminal Cases, focusing on Decision Number 196/Pid.Sus/2021/PN. Jkt.Utr. Crime victims' rights are addressed by Law Number 8 of 1981, specifically in Articles 98 to 101 of the Code of Criminal Procedure (KUHAP), while compensation in Civil Law is governed by Article 1365 of the Civil Code. However, seeking compensation through civil law procedures can be time-consuming. A normative juridical approach was employed, utilizing statutory analysis and a case study method. Primary, secondary, and tertiary legal materials provided secondary data. The analysis, framed by justice theory and legal certainty theory, reveals that merging compensation lawsuits with criminal cases under Article 98 of the Criminal Procedure Code can expedite resolution. Prerequisites for consolidation include alignment of defendant actions with charges, resulting losses, and a request from the aggrieved party to the Judge. This study underscores the potential of combining cases to streamline compensation claims, offering implications for enhancing victims' access to justice within the legal system.